DARE Newsletter, Vol. 18, No. 4 - Goebel, George; DARE (Dictionary of American Regional English, 2015)
Contents: "The News from DARE" by George Goebel; "Notes on Words" by George Goebel; "Discount on Digital DARE"; "DARE Helps NEH Celebrate Fifty Years"; "Staff Member Profile--Trevor Wells Fraser"; "DARE After Dark"; " 'Words Count' Exhibition"
Quarterly newsletter of the Dictionary of American Regional English
Keywords: Americanisms; Dictionaries; Lexicography; Regional English; English Language--Dialects--United States